Rooting Generation Alpha Challenges and Guiding Them toward Islamic Education in Digital Age - Hariyanto; Abas Mansur Tamam; Abuddin Nata; Kisti Robati (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Generation Alpha is growing within a digital environment that increasingly shapes how children learn, communicate, behave, and develop their identities. While digital technology offers substantial educational opportunities, its uncontrolled influence may also contribute to instant gratification, weakened social interaction, declining appreciation of learning processes, reduced religious commitment, and other developmental concerns. This study aims to examine the major challenges faced by Generation Alpha in the digital age and formulate an Islamic educational framework for addressing these challenges. A qualitative library research design was employed by analyzing academic articles, scholarly opinions, books, and Islamic educational references concerning Generation Alpha, digital environments, child development, and Islamic education. The collected information was documented, reduced, thematically organized, compared across sources, and interpreted using the Miles and Huberman analytical framework. The findings indicate that the problems of Generation Alpha are interconnected across cognitive, affective, and psychomotor dimensions and are influenced by the interaction between technological exposure, social and material environments, and patterns of upbringing. Weak religious commitment and fragile personality formation emerge as central concerns underlying several behavioral and developmental problems. The study proposes an integrated Islamic educational framework grounded in Aqidah, Akhlaq, and Fiqh, complemented by intellectual, social, and psychomotor development and responsible technology use. The study contributes a holistic conceptual perspective for guiding Generation Alpha while recognizing the need for future empirical research to examine its applicability in diverse educational settings.